Bergen insomnia scale for adults: The psychometric features of the Turkish version - ERGÜN, AYŞE (My University, 2023)
Objective: Insomnia is an important health problem affecting physical, spiritual and social well-being of individuals negatively and it should be early diagnosed as well. The purpose is to appraise the psychometric features of the Turkish version of the Bergen Insomnia Scale (BIS) for adults.Methods: A total of 495 adults were included in the methodological study in Turkey. Turkish form of BIS was designed within the scope of study conducted in adolescent sample. Construct validity was appraised with exploratory, confirmatory factor analysis, convergent and discriminant validity. Internal-consistency and test-retest analysis were used for reliability.Results: According to results of explanatory, confirmatory factor analysis; it was identified that BIS showed a two-factor structure as daytime symptoms (a=.85) and nocturnal symptoms (a=.80). Item-total correlations were found as >=.59 and test-retest correlation as .83.Conclusions: The Turkish version of the Bergen Insomnia Scale for adults was assessed as valid and reliable.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Insomnia; reliability and validity; adult; SLEEP; ASSOCIATION; PREVALENCE; RELIABILITY; ALPHA; OMEGA; PAIN; Insomnia; reliability and validity; adult